PENGARUH PELAYANAN JASA TERHADAP LOYALITAS ANGGOTA DAN KEPUASAN ANGGOTA SEBAGAI VARIABEL INTERVENING PADA KOPERASI RIAS KECAMATAN PURWODADI KABUPATEN MUSI RAWAS - Supriyanto Supriyanto; Diana Okta Vianingsih (LPPM UNIVERSITAS BINA INSAN, 2020)
The research objective was to determine the effect of services on the loyalty of members of the RIAS Savings and Loans Cooperative through member satisfaction as an intervening variable. This type of research is descriptive using a qualitative approach. The research sample was 100 members of the RIAS Savings and Loans Cooperative. The main instrument for data collection was a questionnaire and the results of the questionnaire were analyzed using pathway model analysis. The results showed that (a) services have a positive effect on member satisfaction because the significant value generated in the path analysis model I is 0.000 <0.050, (b) services have a positive effect on member loyalty because the significant value generated in the path analysis model II is equal to 0.000 <0.050, (c) member satisfaction has a positive effect on member loyalty because the significant value generated in the path analysis model II is 0.000 <0.050, (d) services and member satisfaction simultaneously have a positive effect on member loyalty because the results of the F test are 503,286 > The critical value of table F is 3.09 and (e) services have a positive effect on member loyalty through the intervening variable member satisfaction because the value of the direct effect of the service variable on member loyalty is 0.444 <0.4890 as the total value of the multiplication of the value of the influence of service variables services to satisfaction members with the value of the influence of Member Satisfaction on Member Loyalty.